Uwarunkowania przepływu kapitału zagranicznego w ramach BIZ w krajach o zróżnicowanym rozwoju gospodarczym (w Polsce, Indiach, USA) - Nowak, Alicja; Kociszewska, Irena (Conditions of Foreign Capital Flows Based on Foreign Direct Investment the Case of Poland, India and the USA - the Countries at a Various Stage of Economic Development, 2005)
The aim of this paper is to analyse Polish, Indian and American foreign direct investment (FDI) in Poland, India and the USA. Taking in consideration the USA, is as very well developed country, which became a lieder in foreign investment process. Both the USA and India show flexibility in adjusting investment incentives to each state in contrast to Poland. In Poland, there is a lack of treating investment incentives on a broad basis, lack of promotion of the country abroad. To sum up, capital expenditure is a huge chance for India and Poland to transfer new organization solutions, technology, decrease the rate of unemployment and especially increase of export.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 234-246